Formulation of re-dispersible dry o/w emulsions using cellulose nanocrystals decorated with metal/metal oxide nanoparticles. Issue 51 (29th September 2021) - Shaheen, Tharwat I.; Capron, Isabelle
Abstract : Schematic diagram for the detailed preparation of dry eicosane o/w emulsions. Abstract : This study describes for the first time the preparation of re-dispersible surfactant-free dry eicosane oil emulsion using cellulose nanocrystals (CNCs) using the freeze-drying technique. Surface properties of CNCs constitute a critical point for the stability of o/w emulsions and thus can affect both the droplet size and dispersion properties of the emulsion. Therefore, surface modification of CNCs was performed to understand its effect on the size of the obtained re-dispersible dry o/w eicosane emulsion. Decoration of the CNC surface with metal and metal oxide nanoparticles was conducted through the available alcoholic groups of glycosidic units of CNC, which played a dual role in reducing and stabilizing nanoparticles. Of these nanoparticles, silver (AgNPs), gold (AuNPs), copper oxide (CuO-NPs), and iron oxide (Fe3 O4 -NPs) nanoparticles were prepared via a facile route using alkali activated CNCs. Thorough characterizations pertaining to the as-prepared nanoparticles and their re-dispersible dry eicosane o/w emulsions were investigated using UV-vis spectroscopy, TEM, XRD, particle size, zeta potential, and STEM. Results confirmed the ability of CNCs to stabilize and/or reduce the formed nanoparticles with different sizes and shapes. These nanoparticles showed different shapes and surface charges accompanied by individual morphologies, reflecting on the stability of the re-dispersed dry eicosane emulsions with droplet sizes varying from 1.25 to 0.5 μm.